PENGARUH KORUPSI, KUALITAS PEMBANGUNAN MANUSIA DAN PENANAMAN MODAL ASING (FDI) TERHADAP KEMISKINAN DI ASEAN - Fika Gumala; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to find out how the effects of corruption, the quality of human development and foreign investment on poverty in ASEAN. The data used is secondary data in the form of a panel of data from 2012 to 2016, with data collection techniques are library studies obtained from relevant institutions and agencies. The variables used are Corruption, Quality of Human Development, Foreign Investment and Poverty. The research methods used are: (1) Pooled Analysis (2) Determination Coefficient (3) T Test (4) Test F. The results of the study show that corruption has a significant positive effect on poverty. This means that increasing corruption tends to lead to increasing poverty. While the quality of human development has a significant negative effect on poverty. That is, the increasing quality of human development tends to cause more poverty. Meanwhile, foreign investment has no influence on poverty. This means that the increasing number of foreign investments cannot reduce poverty.